Attenuation of antidepressive effects of transcranial magnetic stimulation in patients whose medication includes drugs for psychosis. (October 2020) - Hebel, Tobias; Abdelnaim, Mohamed; Deppe, Markus; Langguth, Berthold; Schecklmann, Martin
Objective: To assess whether concomitant antipsychotic treatment has an influence on the antidepressive effects of repetitive transcranial magnetic stimulation (rTMS). Methods: We analyzed severity of depression before and after treatment with rTMS in a sample of 299 depressed in- and outpatients in retrospect in relation to treatment with drugs for psychosis. The sample consisted of real-life patients in a tertiary hospital. We ran group contrasts between the group taking and the group not taking drugs for psychosis, testing for differences in Hamilton Depression Rating Scale (HDRS). Effect sizes for HDRS group contrasts were reported as Cohen's d and number needed to treat (NNT) calculated from d . To control for group differences we repeated the Student t-tests for the change in the HDRS using analysis of covariance including confounding variables. Results: Depressed patients taking drugs for psychosis showed significantly less amelioration of depressive symptoms after rTMS treatment as measured by absolute and relative change in HDRS with small effect size or NNT of 4.5 to 8.4, respectively. Controlling significant group contrasts revealed that the effect of taking drugs for psychosis does not depend on age, number of applied TMS pulses, type or severity of depression at baseline, comorbidities or differences in the intake of additional medication. Conclusion: Drugs for psychosis attenuate antidepressive effects of rTMS independently of confounding factors. The effect is statistically significant and of potentially great clinical importance. The exact mechanism remains to be elucidated and further studies are warranted.